A Systematic Literature Review on the Development of Technology-Based Interactive Learning Modules for Students with Physical Disabilities - Desniar Desniar; Nurhastuti Nurhastuti; Ahman Fauzan; Antoni Tsaputra; Desniar Desniar; Nurhastuti Nurhastuti; Ahman Fauzan (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This study focused on the design and implementation of technology-based interactive learning modules for physically challenged students. It was based on the lack of organized and pedagogically meaningful digital learning modules in special education. The comparative analysis of citation data was performed in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses framework using bibliometric methodology. From a total of 142 records screened, we included 7 studies for qualitative synthesis. The results suggested that interactive learning technologies, such as assistive technology, web-based platforms, augmented reality, virtual reality, and motion-based systems, enhanced accessibility to learning material but also contributed positively with student engagement and skill development. These technologies contributed on cognitive and motor learning outcomes and created really inclusionary adaptive teaching environments. However, the findings also expose that most of studies have primarily focused on technology tools only rather than curriculum design according to structured instructional module. The authors suggested that ambitious interactive learning modules should be designed in a systematic and pedagogically integrated manner. Future research needs to focus on blending the unique aspects of instructional design with technological innovation in order to more readily promote effectiveness for practitioners working within special education.